Commodity risk assessment of black pine (Pinus thunbergii Parl.) bonsai from Japan. (15th May 2019) - ,; Bragard, Claude; Dehnen‐Schmutz, Katharina; Di Serio, Francesco; Gonthier, Paolo; Jacques, Marie‐Agnès; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; et al.
Abstract: The EFSA Panel on Plant health was requested to deliver a scientific opinion on how far the existing requirements for the bonsai pine species subject to derogation in Commission Decision 2002/887/EC would cover all plant health risks from black pine ( Pinus thunbergii Parl.) bonsai (the commodity defined in the EU legislation as naturally or artificially dwarfed plants) imported from Japan, taking into account the available scientific information, including the technical information provided by Japan. The relevance of an EU‐regulated pest for this opinion was based on: (a) evidence of the presence of the pest in Japan; (b) evidence that P. thunbergii is a host of the pest and (c) evidence that the pest can be associated with the commodity. Sixteen pests that fulfilled all three criteria were selected for further evaluation. The relevance of other pests present in Japan (not regulated in the EU) for this opinion was based on (i) evidence of the absence of the pest in the EU; (ii) evidence that P. thunbergii is a host of the pest; (iii) evidence that the pest can be associated with the commodity and (iv) evidence that the pest may have an impact in the EU. Three pests fulfilled all four criteria and were selected for further evaluation ( Crisicoccus pini, Sirex nitobei and Urocerus japonicus ). For the selected 19 pests, the risk mitigation measures proposed in the technical dossier were evaluated. Limiting factors on the effectiveness of the measures were documented. For each of the 19 pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including any uncertainties. For all evaluated pests, the median likelihood of the pest freedom is 99.5% or higher and within the 90% uncertainty range it is 99% or higher.